2022
DOI: 10.1186/s13102-022-00443-z
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for injuries in female soldiers: a systematic review

Abstract: Background Female soldiers form an integral part of any modern defence force. Previous reports have highlighted that female soldiers report injuries at higher rates than male personnel. One possible reason for this is an actual difference in underlying injury rates, purported to be due to several factors, including levels of fitness. The aim of this review was to determine risk factors for injuries in female soldiers. Methods A systematic search wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 68 publications
(254 reference statements)
1
6
0
Order By: Relevance
“…Thus, our identified associated factors cannot be seen as predictive risk factors as the design only gives evidence of associations. At the same time, the results corroborate previous findings in female military personnel, 20 , 22 , 23 which strengthen our findings. However, we have not explored the situation for male recruits undergoing BMT and can therefore not know if our findings are sex specific or due to other factors.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Thus, our identified associated factors cannot be seen as predictive risk factors as the design only gives evidence of associations. At the same time, the results corroborate previous findings in female military personnel, 20 , 22 , 23 which strengthen our findings. However, we have not explored the situation for male recruits undergoing BMT and can therefore not know if our findings are sex specific or due to other factors.…”
Section: Discussionsupporting
confidence: 93%
“…This is in line with results from systematic reviews where previous injuries and poor physical performance are found to be significant predictors of MSD in military personnel. 12 , 13 , 22 Physical fitness level might be even more important for female soldiers as low physical fitness was found to be a stronger predictor of MSD in women than in men. 35 The higher injury rate in women compared to men during BMT could actually be due to differences in average fitness levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Orr et al ( 26 ) postulated that if female service members were required to carry the same absolute loads as male service members, the relative loads would be greater, as demonstrated by this study. While this study focussed on the US Marine Corps, these findings are relevant across the tactical spectrum, given the occupational requirement for load carriage and the increasing numbers of female personnel ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the concept of either a longer training period of equivalent content or ability group-based training (stratified by fitness level) may be more beneficial regardless of sex. Numerous studies have shown that it is not sex, which is the primary injury risk factor, but aerobic fitness (1)(2)(3)18,23,33). Furthermore, aerobic fitness and muscular strength, which are generally lower in female members (2,23), are both strongly associated with load carriage performance (28,29,31).…”
Section: Tablementioning
confidence: 99%